Repercussões do estresse em trabalhadores de enfermagem na atenção às pessoas com covid-19 em um hospital público do recôncavo baiano - Menezes, Carla Barbosa de (2023)
Stress in nursing workers is a contemporary topic of debate and investigation. Nursing is a category exposed to high levels of pressure and stress, which can trigger mental disorders characterized by anxiety symptoms, memory and concentration difficulties, fatigue, insomnia and stress. This study aimed to analyze the repercussions of stress on Nursing workers in the care of people with Covid-19 in a public hospital in the Bahian reconcavo. This is a qualitative exploratory research. Data collection took place from January to February 2023 through semi-structured interviews. Data were analyzed using word clouds and similarity trees and content analysis. After careful reading and analysis of the data, three categories were apprehended: characterization of the study participants, Meaning and experience of Stress in the eyes of Nursing workers in the hospital area who worked in the pandemic period of Covid-19, and Repercussions of stress in the hospital routine of nursing workers working in the care of people with Covid-19. The study indicates that nursing workers were exposed to stress when caring for patients with covid- 19, intensified in the care of patients in a serious situation. Stressful experiences reported in the work environment are: work overload, lack of planning, speed in carrying out tasks, fatigue, lack of participation in decision-making, lack of support from management, technological changes, excessive responsibility without preparation, conflicts interpersonal and professional devaluation. These stressful situations represent less satisfaction at work, greater tension and low self-esteem, causing stress. Nursing is a stressful profession, which requires a lot of responsibility for the lives of others and which deals with suffering, which requires a great performance of their duties from the professional, increasing the occurrence of physical and psychosocial exhaustion. Contact with stressors has repercussions on the daily lives of nursing workers, generating emotional exhaustion and demotivation that were intensified in the Covid-19 pandemic. The mental repercussions stand out as: exacerbated fear, hopelessness, despair, isolation measures, depression, anxiety even same suicidal behavior. It is recommended the creation of policies and actions related to mental health and the construction of strategies for the mental health care of these workers in order to prevent and minimize illness in the work environment. It is important to invest in studies on the subject to expand the discussion on the subject and strengthen attention to the worker's mental health.